DEEPEN, Western DAS Branch - Baird, Alan F.; Wuestefeld, Andreas; Goertz-Allmann, Bettina; Oye, Volker (GFZ Data Services, 2024)
Abstract From June to August 2021 the DEEPEN project deployed a dense seismic network across the Hengill geothermal area in southwest Iceland to image and characterize faults and high-temperature zones at high resolution. The nodal network comprised 498 geophone nodes spread across the northern Nesjavellir and southern Hverahlíð geothermal fields and was complemented by an existing permanent and temporary backbone seismic network of a total of 44 short-period and broadband stations. In addition, two fiber optic telecommunication cables near the Nesjavellir geothermal power plant were interrogated with commercial DAS-interrogators. The here published dataset contains a subset of the downsampled DAS-recordings from the western fiber optic array. The original data were downsampled from 2000Hz to 250 Hz using the das-convert tool (https://doi.org/10.5880/GFZ.2.1.2021.005). Note that there was a problem with the GNSS timing in the original recorded data which caused significant temporal drift. This has mostly been corrected in the downsampled data, but some residual timing error may exist. Waveform data is available from the GEOFON data centre, under network code 1D, and is fully open.